Analisis Upah Proses Berdasarkan Putusan Mahkamah Konstitusi Nomor 37/PUU-XI/2011, Surat Edaran Mahkamah Agung Nomor 3 Tahun 2015 dan Surat Edaran Nomor 3 Tahun 2018 (Studi Kasus Putusan Pengadilan Hubungan Industrial Jakarta Pusat Nomor 255/Pdt.Sus-PHI/2017 jo. Putusan Mahkamah Agung Nomor 499 K/Pdt.Sus-PHI/2018). - Jesslyn Gressella; Andari Yurikosari (Jurnal Hukum Adigama, 2019)
This study has title "Analysis of Process Wage Based on Constitutional Court Decision Number 37 / PUU-XI / 2011, Supreme Court Circular Letter Number 3 Year 2015 and Circular Letter Number 3 Year 2018 (Case Study of Central Jakarta Industrial Relations Court Decision Number 255 / Pdt.Sus -PHI / 2017 Jo. Supreme Court Decision Number 499 K / Pdt.Sus-PHI / 2018). This study uses the type of normative legal research or literature on labor agreement theory and legal certainty theory. The approach used in this research is the law approach which is completed with interview data. The wage of process given to workers in the discussion of this study is not in accordance with statutory regulations. The judge decides the case based on the Supreme Court Circular Letter Number 3 Year 2015 and Circular Letter Number 3 Year 2018. In the author's opinion, this case study can be the application of the law regarding process wages to be uncertain and unfair for workers. The application of process wages should be appropriate and fair in order to create legal certainty in the Industrial Relations Court